2013
DOI: 10.1002/cvde.201207039
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma ALD of Titanium Oxide

Abstract: Atmospheric-pressure plasma atomic layer deposition (APP-ALD) of TiO x at room temperature is reported for the first time. Layer properties of the APP-ALD-grown TiO x are compared to those reported for the low-pressure plasma ALD of TiO x . The contribution of parasitic CVD to the process is discussed. The application of the resulting TiO x layers as electron-extraction interlayers in inverted organic solar cells (OSCs) is demonstrated. The characteristics of OSCs based on APP-ALD-grown TiO x are similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…The refractive index of the TiO 2 film increased from 1.86 to 1.98 by prolonging the plasma exposure time (Table ), further indicating the role of plasma reactive species in controlling film properties. The plasma exposure time in this study was in the order of few milliseconds, which is considerably shorter than the plasma duration in most of the previous studies reported in the literature . The lowest plasma exposure time during a ALD process was reported by Poodt et al for Al 2 O 3 deposition by spatial ALD (100 ms).…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…The refractive index of the TiO 2 film increased from 1.86 to 1.98 by prolonging the plasma exposure time (Table ), further indicating the role of plasma reactive species in controlling film properties. The plasma exposure time in this study was in the order of few milliseconds, which is considerably shorter than the plasma duration in most of the previous studies reported in the literature . The lowest plasma exposure time during a ALD process was reported by Poodt et al for Al 2 O 3 deposition by spatial ALD (100 ms).…”
Section: Resultsmentioning
confidence: 50%
“…The GPC value of ALD TiO 2 layers grown at low pressures and low temperatures (<100°C) with TTIP and O 2 plasma were reported to be between 0.05 and 0.19 nm when using different plasma sources and temperatures . Plasma‐enhanced ALD of titanium oxide at atmospheric pressure was reported by Theirich et al They used TTIP and Ar/O 2 plasma in a DBD reactor and obtained a GPC value of 0.16 nm. However, they pointed out that at least one fourth of the growth is CVD reaction‐induced due to residual moisture in their reactor.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, PEALD exhibits a significantly higher TiO 2 deposition rate, at lower temperatures (150 • C), than does conventional ALD, as was reported for O 2 -PEALD in comparison to ALD of TiO 2 using water and ozone [100]. Later, Theirich et al demonstrated the APP ALD of TiO x layers at room temperature for the first time using O 2 /Ar flow [101]. The authors concluded that the metastable excited argon atoms are essential in the TTIP precursor decomposition because the growth was independent of the presence of oxygen.…”
Section: Plasma-enhanced Atomic Layer Depositionmentioning
confidence: 85%
“…Only recently, atmospheric pressure plasmas have been used in (spatial) ALD of oxides. 11,12 In this paper, we demonstrate for the first time spatial atmospheric plasma enhanced ALD of silver films from Ag(fod)(PEt 3 ), triethylphosphine (6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octanedionate) silver(I), and an N 2 -H 2 plasma. This process combination allows us to accurately control film morphology at processing speeds up to 0.8 nm/min for all atmospheric conditions compared to a maximum of 0.15 nm/min as reported by Kariniemi et al for the case of conventional plasma-enhanced ALD.…”
Section: Introductionmentioning
confidence: 89%